(untitled) (Medico Legal Update, 2021)
Exclusive breastfeeding is very important for babies to maintain their immune system, brain intelligence, emotion stability and to protect babies from various diseases that are causes of death. Breastfeeding will also benefit the mother, which will reduce blood loss during menstruation, restore maternal weight as before pregnancy, reduce the risk of breast cancer, and uterine cancer. The purpose of this study was to determine the influences of antenatal care, postnatal care and early initiation of breastfeeding on an exclusive breastfeeding pattern. The samples used in this study were mothers who had babies aged 7-12 months in June to August 2018 as many as 48 respondents in the working area of Manukan Kulon Health Center in Surabaya. This study used the descriptive and bivariate analyses. The obtained results were antenatal care (p = 0.001), postnatal care (p = 0.002) and early initiation of breastfeeding (p = 0,000). During pregnancy the majority of mothers make complete antenatal care visits with a frequency of 10 times, antenatal care is very important for mothers, especially the pattern of breastfeeding. In addition to the importance of antenatal care visits, mothers who have given birth and are entering the postnatal care phase are required to make postnatal care visits. Socialization from health workers and the support of closest people are required in order to achieve the exclusive breastfeeding.